Experiences of care home staff in the delivery of heart failure care: a grounded theory - Gary Mitchell; James McMahon; Lana Cook; Oonagh McCloy; Paul Tierney; David R Thompson; Laura Creighton; Stephanie Craig; Elizabeth Henderson; Loreena Hill; Jan Cameron; Doris Yu; et al. (BMC Geriatrics)
Abstract Background Heart failure is a complex syndrome affecting 64 million people globally, with an average patient age of 76 years. Management challenges include medication titration difficulties and patient self-management issues. Care homes, housing approximately 20% of residents with heart failure, face unique challenges in managing this condition. This study aimed to investigate care home staff experiences in supporting residents with heart failure. Methods A Glaserian grounded theory approach was employed to explore perceptions, challenges, and strategies used by care home staff in supporting residents with heart failure. Twenty care home staff members from Northern Ireland, with varied roles and experience levels, participated in online semi-structured interviews. These interviews were audio-recorded and transcribed verbatim. Data collection and analysis occurred concurrently, following theoretical sampling principles, between February 2023 and March 2024. A three-stage coding process (open, axial, and selective) was used for analysis. Rigour was ensured through member checking, data source triangulation, and reflexivity. Ethical approval was obtained prior to data collection. Results Three main categories were developed from the data: (1) Training, (2) Support, and (3) Communication. Training revealed that care home staff received limited education on heart failure management, primarily focused on acute settings rather than the chronic care needed in care homes. Support highlighted the various facilitators and barriers staff faced in making clinical decisions regarding heart failure care. Communication addressed the experiences of staff in engaging residents and their families about managing heart failure. These categories linked to the core category of (C) Empowerment, which encompassed the challenges staff faced in training, support, and communication. Empowerment illustrated how staff navigated these obstacles to provide effective heart failure care within the unique context of care homes. Discussion This study highlights significant challenges in managing heart failure in care homes, including inadequate training, limited professional development, and insufficient support systems. Key barriers include a lack of specialist education tailored to long-term care settings and restricted access to heart failure specialists. Effective communication and proactive care were identified as critical needs, alongside holistic care approaches. Addressing these gaps through targeted education, specialist integration, and evidence-based strategies could empower staff, optimise care quality, and potentially improve outcomes for residents.